The Effect of Promotions and Discount Offers on the Brand Image of Rinkadaily - AFIFAH, Ainun; SAKTI, Intan Widuri (PT Keberlanjutan Strategis Indonesia, 2024)
This research aims to determine the effect of promotions and discount offers on the Rinkadaily brand image. The research method used is descriptive and verification, using a quantitative approach to explain the relationship between the investigated variables. This research used a sample of 97 respondents. Sampling used a non-probability sampling technique with a purposive sampling technique with the characteristics of respondents who had previously purchased Rinkadaily products and were willing to fill out the questionnaire provided. The test tools used are research instrument tests and multiple linear regression analysis. The research results show that based on the coefficient of determination test between these two variables, the promotion variable partially produces a promotional effect of 0.24% and a discount offer of 2.56%. It shows that promotions and discount offers partially influence the brand image. The research results also show that the correlation value is positive. It indicates that the better the promotions and the more frequent discounts Rinkadaily offers, the better the Rinkadaily brand image will be. The conclusion is that promotions and discount offer partially and simultaneously significantly and positively affect the Rinkadaily brand image.